1986
DOI: 10.3109/00365528609003105
|View full text |Cite
|
Sign up to set email alerts
|

The Trophic Effect on the Pancreas of Long-Term Continuous Intravenous Infusion of Secretin and a Cholecystokinin-Like Peptide in Rats

Abstract: Rats were treated for 5 days with continuous intravenous infusion of different doses of secretin and Thr28Nle31CCK25-33 (CCK-LP) alone and combined. The trophic effect on the pancreas was evaluated by means of pancreatic weight and contents of DNA, RNA, and protein. The acute effects on pancreatic protein secretion were studied in anesthetized rats. The findings generally confirmed the trophic effects of secretin and CCK-like peptides on the pancreas. No convincing evidence of potentiation was found between sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…DNA and RNA were extracted and analyzed as described earlier (10,19). Results were expressed as total content per pancreas.…”
Section: Dna and Rnamentioning
confidence: 99%
See 1 more Smart Citation
“…DNA and RNA were extracted and analyzed as described earlier (10,19). Results were expressed as total content per pancreas.…”
Section: Dna and Rnamentioning
confidence: 99%
“…A potentiating interaction is here defined as a response to a combination of stimulants which are significantly greater than the sum of the responses to the individual agents given separately. Calculations were performed as described earlier (9,10).…”
Section: Statistics and Calculationsmentioning
confidence: 99%
“…VIP also stimulates adenylate cyclase activity and cell proliferation in keratinocytes (Haegerstrand et al, 1989).…”
Section: Bradykininmentioning
confidence: 97%
“…Cholecystokinin has trophic effects on normal pancreas, as shown by measurements of pancreatic weight and DNA synthesis (Haarstad et al, 1986;Douglas et al, 1989). It can also directly stimulate the growth of rat gastric cancer cells in vitro (Kobori et al, 1982) and has been implicated in the growth of gut tumours (Lamers & Jansen, 1988;Hoosein et al, 1990).…”
Section: Cholecystokininmentioning
confidence: 99%
“…Several studies have demonstrated that CCK can increase pancreatic size (96). Exogenous administration of CCK increased pancreatic mass in hamsters and rats (27,28,68). In the rat, CCK1 receptor but not CCK2 receptor agonists increased pancreatic mass by increasing the number of cells comprising the exocrine pancreas (72).…”
Section: Trophic Effect Of Cck On the Pancreasmentioning
confidence: 98%